Pengaruh Kepemilikan Pemerintah, Kecakapan Manajerial, Investment Opportunity Set, dan Capital Intensity Ratio terhadap Effective Tax Rate (Studi Empiris Perusahaan yang Terdaftar pada Indeks Saham IDX30 di Bursa Efek Indonesia Periode 2018-2020) - Alda Khoirun Nisa'; Kurnia Kurnia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to determine the effective tax rate with government ownership, managerial skills, investment opportunity set, and capital intensity ratio. This study uses a quantitative method with the effective tax rate as the dependent variable. The company's effective tax rate calculation is used as a proxy in assessing the company's tax burden. This study uses secondary data in the form of financial statements of companies listed on the IDX30 stock index on the Indonesia Stock Exchange (IDX) in the period 2018 to 2020. The sampling technique used a purposive sampling technique and obtained as many as 31 company sample data points. The hypothesis was tested using multiple linear regression analysis with the Eviews program. The result shows that the variables GOV, KM, IOS, and CIR simultaneously affect on ETR. Based on the results of the t test, it can be cocluded that partially the GOV, IOS, and CIR variables have no significant effect on ETR., while the KM variables have a significant effect on ETR. The result of the calculation of the coefficient of determination show that the influence given by the independent variable to the dependent variable is 40,72% while the remaining 59,28% is influenced by other variables not included in this study.